The most primitive CM chondrites, Asuka 12085, 12169, and 12236, of subtypes 3.0-2.8: Their characteristic features and classification - Kimura, M.; Imae, N.; Komatsu, M.; Barrat, Jean-alix; Greenwood, R. C.; Yamaguchi, A.; Noguchi, T. (Polar Science, 2020)
CM chondrites (CMs) are the most abundant group of carbonaceous chondrites. CMs experienced varying degrees of secondary aqueous alteration and heating that modified or destroyed their primitive features. We have studied three chondrites, Asuka (A) 12085, A 12169, and A 12236. Their modal compositions, chondrule size distributions, and bulk composition indicate that they are CMs. However, the common occurrence of melilite in CAIs and glass in chondrules, abundant Fe-Ni metal, the absence of tochilinite-cronstedtite intergrowths, and almost no phyllosilicates, all suggest that these chondrites, especially A 12169, experienced only minimal aqueous alteration. The textures and compositions of metal and sulfides, the lack of ferroan rims on AOA olivines, the compositional distribution of ferroan olivine, and the Raman spectra of their matrices, indicate that these chondrites experienced neither significant heating nor dehydration. These chondrites, especially A 12169, are the most primitive CMs so far reported. The degree of the alteration increases from A 12169, through A 12236, to A 12085. We propose the criteria for subtypes of 3.0-2.8 for CMs. A 12169, A 12236, and A 12085 are classified as subtype 3.0, 2.9, and 2.8, respectively. The oxygen isotopic composition of the Asuka CMs is consistent with these samples having experienced only a limited degree of aqueous alteration. The CM and CO groups are probably not derived from a single heterogeneous parent body. These chondrites are also of particular significance in view of the imminent return of sample material from the asteroids Ryugu and Bennu.